Etika Komunikasi Citizen Journalism Di Media Internet Perspektif Islam: Analisis Konten Topik Pilihan Demo 4 November 2016 pada Blog kompasiana.com - Fitri Fitri (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2016)
Citizen journalism is a journalistic activities undertaken by the citizens. Citizen journalism can be accessed via internet anywhere and anytime. Application of communication ethics in reporting by citizens is one of the issues that need to be highlighted. Moreover, citizens are not professional journalists who received special training in journalism. Citizens prefer the ability and experience alone in covering and disseminating information on the internet. In this research reveal how communication ethics of citizen journalism in ‘Topik Pilihan Demo 4 November blog kompasiana.com” according to the Islamic perspective. Data obtained by observation with a qualitative approach, as well as critical discourse analysis. As the result of this reseach, citizen journalism has the ability of fairness, free and responsible,also constructive criticism. Nevertheless citizen journalism still has weaknesses in accuracy andIslamic ccommunication ethics.***Citizen journalism (jurnalisme warga) merupakan kegiatan jurnalistik yang dilakukan oleh warga. Citizen journalism dapat diakses melalui internet di mana saja dan kapan saja. Penerapan etika komunikasi dalam pemberitaan oleh warga menjadi salah satu masalah yang perlu disoroti. Terlebih warga bukanlah jurnalis profesional yang mendapat pelatihan khusus jurnalisme. Penelitian ini mengungkap bagaimana etika komunikasi citizen journalism pada ‘Topik Pilihan Demo 4 November blog kompasiana.com” dalam perspektif Islam. Data diperoleh dengan dokumentasi dengan pendekatan kualitatif, serta analisis wacana kritis. Hasil penelitian ini menunjukkan bahwa citizen journalism memiliki kemampuan fairness, bebas bertanggungjawab dan kritik konstruktif. Meski demikian citizen journalism masih mempunyai kelemahan dalam akurasi dan etika komunikasi islami.